SPH 해석기법을 이용한 Cu와 CP-Ti 고속 충돌 접합 단면의 형상학적 평가 - 박기환(Ki Hwan Park); 강범수(Beom Soo Kang); 김정(Jeong Kim) (항공우주시스템공학회지, 2019)
The existence of different thermodynamic properties results in various undesirable effects, such as thermal deformation and residual stress, in heat-welding processes. The solid-state junction, by using explosive or electromagnetic forces, i.e., high-velocity impact welding without employing heat is advantageous in joining materials with different thermodynamic properties. In the solid-state junction, the joining is performed within a short time, a high velocity and large deformations are accompanied by interfacial surfaces. The numerical analysis models play an important role in the understanding of the mechanism of high-velocity impact welding. However, in the analysis of high velocity and large deformations, the conventional Lagrangian method has low reliability due to the occurrence of entanglements. In this study, high-velocity impact welding between Cu and CP-Ti with different thermodynamic properties was performed using a un-gridded numerical method, SPH (Smoothed Particle Hydrodynamics), and interfacial morphology occurred. As a result of the analysis, the interfacial morphology was confirmed and the compared degree of shape (straight, vortex), period, length, and so on appeared differently depending on the relationship between the parameters (impact angle and speed). 열을 이용한 접합은 소재 간 열역학적 차이에 의한 열 변형 및 잔류응력 등 원하지 않은 결과를 야기한다. 폭발력 또는 전자기력을 이용한 고상 접합은 열이 사용되지 않아 열역학적 차이가 있는 소재접합에 이점이 있다. 이때, 해당 접합은 짧은 시간 내(${μ}s$) 이루어지며, 접합면에서 고속 및 대 변형이 동반된다. 수치해석 모델은 고속 충돌 접합 메커니즘을 이해하는 데 중요한 역할을 수행한다. 하지만 고속 및 대 변형이 나타나는 해석에서 전통적인 라그랑지안 기법은 격자 얽힘이 발생해 결과의 신뢰성이 낮다. 본 연구는 무격자 수치해석 방식의 SPH(Smoothed Particle Hydrodynamics)를 이용하여 열역학적 차이가 있는 Cu와 CP-Ti의 고속 충돌 접합을 수행하였고 경계면 결합 형상이 발생함을 확인하였다. 해석의 결과로 경계면 결합 형상이 매개변수(충돌 속도, 충돌 각도)의 관계에 따라 형상의 정도(직선, 소용돌이), 주기, 길이 등이 다르게 나타나는 것을 확인 및 비교하였다.